2016
DOI: 10.1002/jcu.22399
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic left ventricular changes in patients with gestational diabetes: A speckle tracking echocardiography study

Abstract: Although conventional TTE variables show preserved LV size and function, LV longitudinal strain suggests subclinical myocardial dysfunction in patients with GDM. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 45:20-27, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
(34 reference statements)
3
15
0
Order By: Relevance
“…Maternal cardiovascular indices in GDM were examined previously in four case–control studies. Two studies in 13 and 18 women with GDM, respectively, reported a mild degree of diastolic abnormality both during pregnancy and postpartum 3,4 ; the diastolic changes were subtle and did not fulfil the criteria for adult clinical diastolic dysfunction as per European or American guidelines 10,18 . Similarly, in a previous study by our group involving 161 women with GDM and 483 women with uncomplicated pregnancy at 35–36 weeks' gestation, we found that women with GDM had lower left ventricular diastolic and systolic functional indices with no significant differences in cardiac output, peripheral vascular resistance, left ventricular global longitudinal functional changes or left ventricular mass after adjustment for maternal characteristics 6 .…”
Section: Discussionsupporting
confidence: 66%
“…Maternal cardiovascular indices in GDM were examined previously in four case–control studies. Two studies in 13 and 18 women with GDM, respectively, reported a mild degree of diastolic abnormality both during pregnancy and postpartum 3,4 ; the diastolic changes were subtle and did not fulfil the criteria for adult clinical diastolic dysfunction as per European or American guidelines 10,18 . Similarly, in a previous study by our group involving 161 women with GDM and 483 women with uncomplicated pregnancy at 35–36 weeks' gestation, we found that women with GDM had lower left ventricular diastolic and systolic functional indices with no significant differences in cardiac output, peripheral vascular resistance, left ventricular global longitudinal functional changes or left ventricular mass after adjustment for maternal characteristics 6 .…”
Section: Discussionsupporting
confidence: 66%
“…Just like the essential hypertension, diabetes was also an important factor for stimulating LVR . Meera et al found that pregnant women with gestational diabetes mellitus (DM) had significantly higher LV posterior wall thickness when compared with women without gestational DM. Zhang et al also found that both T2DM patients with well‐controlled blood glucose and those with poorly controlled blood glucose had significantly higher LV wall thickness when compared with the controls.…”
Section: Discussionmentioning
confidence: 92%
“…Exposure of the maternal heart to hyperglycemia for a short period of time parallels the cardiac dysfunction seen in non-pregnant patients after decades of diabetes. In a retrospective study of 18 pregnant women with GDM at the end of the second trimester, the authors demonstrated differences only in GLS with preserved circumferential and radial strain in GDM 25 . Although these data support the findings of the present study, the lack of additional cardiovascular findings may be explained by the retrospective nature of the study, smaller sample size, reduced loading conditions of earlier gestational age at assessment and a shorter period of exposure to hyperglycemia.…”
Section: Discussionmentioning
confidence: 97%